Production, Storage Stability, and Susceptibility Testing of Reuterin and Its Impact on the Murine Fecal Microbiome and Volatile Organic Compound Profile - Castellani, Christoph; Obermüller, Beate; Kienesberger, Bernhard; Singer, Georg; Peterbauer, Clemens; Grabherr, Reingard; Mayrhofer, Sigrid; Klymiuk, Ingeborg; Horvath, Angela; Stadlbauer, Vanessa; Russmayer, Hannes; Miekisch, Wolfram; et al. (Frontiers in Microbiology, 2021)
Background: Probiotics are generally considered as safe, but infections may rarely occur in vulnerable patients. Alternatives to live microorganisms to manage dysbiosis maybe of interest in these patients. Reuterin is a complex component system exhibiting broad spectrum antimicrobial activity and a possible candidate substance in these cases. Methods: Reuterin supernatant was cultured from Lentilactobacillus diolivorans in a bioreactor in a two-step process. Storage stability at -20°C and effect of repeated freeze-thaw cycles were assessed by HPLC. Antimicrobial activity was tested against Clostridium difficile, Listeria monocytogenes, Escherichia coli, Enterococcus faecium, Staphylococcus (S.) aureus, S. epidermidis, Streptococcus (Str.) agalactiae, Propionibacterium acnes and Pseudomonas aeruginosae. Male BALBc mice were gavage fed with reuterin supernatant (n=10) or culture medium (n=10). Fecal volatile organic compounds (VOC) were assessed by gas chromatography mass spectroscopy; the microbiome was examined by 16S rRNA gene sequencing. Results: The supernatant contained 13.4 g/L reuterin (3-hydroxypropionaldehyde; 3-HPA). 3-HPA content remained stable at -20°C for 35 days followed by a slow decrease of its concentration. Repeated freezing/thawing caused a slow 3-HPA decrease. Antimicrobial activity was encountered against S. aureus, S. epidermidis and Str. agalactiae. Microbiome analysis showed no differences in alpha and beta diversity markers. LEfSe analysis identified Lachnospiraceae_bacterium_COE1 and Ruminoclostridium_5_uncultured_Clostridiales_ bacterium (in the reuterin medium group) and Desulfovibrio_uncultured_ bacterium, Candidatus Arthromitus, Ruminococcae_NK4A214_group and Eubacterium_xylanophilum_group (in the reuterin group) as markers for group differentiation. VOC analysis showed a significant decrease of heptane and increase of 3-methylbutanal in the reuterin group. Conclusion: The supernatant produced in this study contained acceptable amounts of 3-HPA remaining stable for 35 days at -20°C and exhibiting an antimicrobial effect against S. aureus, S. agalactiae and S. epidermidis. Under in vivo conditions, the reuterin supernatant caused alterations of the fecal microbiome. In the fecal VOC analysis decreased heptane and increased 3-methylbutanal were encountered. These findings suggest the high potential of the reuterin system to influence the intestinal microbiome in health and disease, which needs to be examined in detail in future projects.